Proteomic Analysis of Interaction between a Plant Virus and Its Vector Insect Reveals New Functions of Hemipteran Cuticular Protein - Liu, Wenwen (The American Society for Biochemistry and Molecular Biology, 2015)

(untitled) (Mol Cell Proteomics)
Numerous viruses can be transmitted by their corresponding vector insects; however, the molecular mechanisms enabling virus transmission by vector insects have been poorly understood, especially the identity of vector components interacting with the virus. Here, we used the yeast two-hybrid system to study proteomic interactions of a plant virus (Rice stripe virus, RSV, genus Tenuivirus) with its vector insect, small brown planthopper (Laodelphax striatellus). Sixty-six proteins of L. striatellus that interacted with the nucleocapsid protein (pc3) of RSV were identified. A virus–insect interaction network, constructed for pc3 and 29 protein homologs of Drosophila melanogaster, suggested that nine proteins might directly interact with pc3. Of the 66 proteins, five (atlasin, a novel cuticular protein, jagunal, NAC domain protein, and vitellogenin) were most likely to be involved in viral movement, replication, and transovarial transmission. This work also provides evidence that the novel cuticular protein, CPR1, from L. striatellus is essential for RSV transmission by its vector insect. CPR1 binds the nucleocapsid protein (pc3) of RSV both in vivo and in vitro and colocalizes with RSV in the hemocytes of L. striatellus. Knockdown of CPR1 transcription using RNA interference resulted in a decrease in the concentration of RSV in the hemolymph, salivary glands and in viral transmission efficiency. These data suggest that CPR1 binds RSV in the insect and stabilizes the viral concentration in the hemolymph, perhaps to protect the virus or to help move the virus to the salivary tissues. Our studies provide direct experimental evidence that viruses can use existing vector proteins to aid their survival in the hemolymph. Identifying these putative vector molecules should lead to a better understanding of the interactions between viruses and vector insects.